Safety and efficacy of fixed-combination travoprost/timolol in patients with open-angle glaucoma or ocular hypertension not controlled with timolol monotherapy - Jordão, Marcelo Lopes da Silva; Hatanaka, Marcelo; Ogundele, Abayomi; Silva, Maria Rosa Bet de Moraes [UNESP]; Vessani, Roberto Murad (Dove Press Ltd, 2014)
To assess the intraocular pressure (IOP)-lowering effect of travoprost 0.004%/timolol 0.5% fixed-dose combination (TRAV/TIM-FC) in patients not achieving the target IOP of ≤18 mmHg while on timolol 0.5% (TIM) monotherapy. A multicenter, prospective, open-label study (NCT01336569) was conducted in patients with open-angle glaucoma or ocular hypertension. Eligible patients were receiving TIM monotherapy with a screening/baseline IOP of 19-35 mmHg in ≥1 eye. TIM was discontinued on the baseline visit day (no washout period) and TRAV/TIM-FC was initiated and administered once daily at 8 pm for 4-6 weeks. The primary efficacy variable was mean change in IOP from TIM-treated baseline to study end, measured by Goldmann applanation tonometry. Results were analyzed by analysis of variance and paired samples t-test (5% significance). A total of 49 patients were enrolled (mean age, 63 [range, 42-82] years; 55.1% White; 73.5% women), and 45 were included in the intent-to-treat (ITT) population. Mean duration of treatment with TRAV/TIM-FC was 31 days. Mean ± standard deviation IOP reduction from baseline (TIM) to the follow-up visit (TRAV/TIM-FC) was -5.0±3.6 mmHg. IOP decreased significantly (P<0.0001) from baseline (22.1±2.6 mmHg) to study end (17.1±3.9 mmHg) in the ITT population, with a mean IOP reduction of 22.3%. Most patients (n=33/45; 73.3%) achieved IOP ≤18 mmHg. Two patients experienced a total of four adverse events (AEs), including a patient who reported one serious AE (enterorrhagia) that was considered unrelated to treatment, and a patient who reported one event each of drug-related redness, pruritus, and foreign body sensation. Most patients (n=47/49; 95.9%) reported no AEs. TRAV/TIM-FC lowered IOP in patients who were not at target IOP while receiving TIM monotherapy, with most patients achieving an IOP ≤18 mmHg with TRAV/TIM-FC. TRAV/TIM-FC was well tolerated in this population.
Keywords: Duotrav®; Intraocular pressure; Primary open-angle glaucoma; Time since diagnosis